Modelling home advantage for individual teams in UEFA Champions League football - Chris Goumas (Elsevier, 2017)
Background: Home advantage (HA) is well documented in a wide range of team sports including association football (soccer). Although much attention has been paid to differences in the overall magnitude of HA between football competitions and across time, few studies have investigated HA at the team level. Methods: A novel method of estimating HA for individual teams, based solely on home performance, was used to compare HA between the highest performing teams and countries in the Union of European Football Associations (UEFA) Champions League over a 10-year period (2003/2004 to 2012/2013). Away disadvantage (AD) was also estimated based on each team's performance away from home. Poisson regression analysis was used to estimate covariate adjusted HA and AD in terms of the percentage of goals scored at home (HA) and conceded away from home (AD). Results: When controlling for differences in team ability, HA did not vary significantly between the 13 selected teams. There was evidence (p < 0.1), however, of between-team variation in AD, ranging from 45% (away advantage) to 68% (away disadvantage). When teams were grouped into the 11 selected countries, both HA and AD varied significantly (p < 0.02) between countries: HA ranged from 52% for Turkish teams to 70% for English teams, while AD ranged from 52% (France) to 67% (Turkey). Conclusion: Differences in style of play and tactical approaches to home and away matches may explain some of the variation in HA and AD between teams from different countries.